2000
DOI: 10.1177/019262330002800214
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 2,4,6-Trinitrotoluene in a Holistic Environmental Exposure Regime on a Terrestrial Salamander, Ambystoma tigrinum

Abstract: ABSTRACT2,4,6-Trinitrotoluene (TNT) is a defense-related environmental contaminant present at high concentrations in soil at some military installations. Tiger salamanders (Ambystoma tigrinum, family Ambystomatidae) were exposed to TNT in a soil matrix and fed earthworms that had also been exposed to TNT via contaminated soil. Such exposure was previously shown to result in significant accumulation of both TNT and TNT metabolites by salamanders. Following 14 days of combined oral and dermal exposures, salamand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
5
22
1
Order By: Relevance
“…Their methodology involved using supplemented RPMI medium and incubating cells at room temperature for 45 min. In contrast to findings by other researchers (Rosenkranz et al, 1992;Johnson et al, 2000), hydrogen peroxide production in our pilot studies was not enhanced by adding PMA. This lack of response may have been due to the use of thioglycollate to elicit the migration of neutrophils into the peritoneal cavity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Their methodology involved using supplemented RPMI medium and incubating cells at room temperature for 45 min. In contrast to findings by other researchers (Rosenkranz et al, 1992;Johnson et al, 2000), hydrogen peroxide production in our pilot studies was not enhanced by adding PMA. This lack of response may have been due to the use of thioglycollate to elicit the migration of neutrophils into the peritoneal cavity.…”
Section: Discussioncontrasting
confidence: 99%
“…The mammalian assay was modified for use with amphibian cells by decreasing the incubation temperature from 37 to 27 C and changing the culture medium from phosphate-buffered saline with calcium and magnesium to APBS. Other published protocols (Rosenkranz et al, 1992;Johnson et al, 2000) recommend adding 0.1 nM-1.0 M phorbol 12-myristate 13-acetate (PMA; Sigma-Aldrich) to the culture medium to stimulate hydrogen peroxide production. In initial trials with cells from tiger salamanders stimulated with i.p.…”
Section: Oxidative-burst Assaymentioning
confidence: 99%
“…Skin was concluded to be important in the primary reduction of TNT. When salamanders were exposed to TNT in soil (1 mg/kg) and fed earthworms exposed to TNT in the same soil, no difference between control and treated animals were observed for weight gain, organ-to-body-weight ratios, function of spleenic phagocytic cells, nor peripheral hematological parameters [219]. However, the liver exhibited heavily pigmented iron-rich phagocytes (melanomacrophages) and growth rate was slower during treatment.…”
Section: Vertebratesmentioning
confidence: 95%
“…The salamander (Ambystoma tigrinum) has been suggested as a bioindicator of effects in the evaluation of toxicity of explosives at contaminated sites [217][218][219]. Dermal exposure was determined to be the most important exposure pathway for uptake of TNT from contaminated soil by the salamander.…”
Section: Vertebratesmentioning
confidence: 99%
“…Numerous studies suggest that MMCs are involved in scavenging of various catabolites and exogenous foreign material (Meseguer et al, 1994). Johnson et al (2000) concluded that MMCs in Ambystoma tigrinum may be associated with in#ammatory responses, including phagocytosis. Other researchers reported scavenging cytotoxic substances, such as ions and free radicals (Sichel, 1988;Zuasti et al, 1989).…”
Section: Discussionmentioning
confidence: 99%